2005
DOI: 10.1002/jbt.20100
|View full text |Cite
|
Sign up to set email alerts
|

Liver prenylated methylated protein methyl esterase is an organophosphate-sensitive enzyme

Abstract: Prenylation and subsequent methylation are essential modifications on a significant proportion of eucaryotic proteins. Proteins such as the G-gamma subunits of G-protein coupled receptors, nuclear lamins, and guanine nucleotide-binding proteins such as Ras are prenylated and undergo methylation. Prenylated methylated protein methyl esterase (PMPMEase) readily hydrolyses the prenylated protein methyl esters, thus making this step reversible and possibly regulatory. Benzoyl-glycyl-farnesyl-cysteine methyl ester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…It shows high-sequence identity and even higher sequence similarity to various mammalian esterases that hydrolyze a wide range of mainly hydrophobic substrates and have molecular weights around 60 kDa [21][22][23]. These features are similar to those of the purified PMPMEase, which shows a molecular weight on SDS-PAGE of about 57 kDa, and both the rat liver [10] and porcine liver in this study show a high affinity for the hydrophobic PC analog ester substrates. The crystal structure of the human isoform, hCE1, reveals complexes of homotrimers at equilibrium with the homohexamers and the catalytic triad of Ser221-His468-Glu354 inside a deep hydrophobic pocket that has a small rigid subsite and a large flexible region [24,25].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…It shows high-sequence identity and even higher sequence similarity to various mammalian esterases that hydrolyze a wide range of mainly hydrophobic substrates and have molecular weights around 60 kDa [21][22][23]. These features are similar to those of the purified PMPMEase, which shows a molecular weight on SDS-PAGE of about 57 kDa, and both the rat liver [10] and porcine liver in this study show a high affinity for the hydrophobic PC analog ester substrates. The crystal structure of the human isoform, hCE1, reveals complexes of homotrimers at equilibrium with the homohexamers and the catalytic triad of Ser221-His468-Glu354 inside a deep hydrophobic pocket that has a small rigid subsite and a large flexible region [24,25].…”
Section: Discussionsupporting
confidence: 66%
“…Organophosphorus pesticides (OPs) [11][12][13], lactones [14], sulfonyl fluorides [15], and chloromethylketones [16] inhibit various serine hydrolases by this mechanism. In previous studies, prenylated methylated protein methyl esterase from rat liver supernatant and brain membranes was inhibited by OPs [10]. Similarly, a prenylation specific esterase from bovine rod outer segment membranes was inhibited by ebelactone B [14].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This substance was used as substrate analogue for the detection of specific PMPMEase activity, because various choline esterases did not hydrolyse BzGFCM. 13 The investigations were performed using PLE isoenzymes 1-6 (with cPLE being identical to PLE-1), commercially available PLE from Fluka and APLE. 18 Conversion was determined at different times using RP-HPLC.…”
Section: Ple Acts As Prenylated Methylated Protein Methyl Esterase (Pmentioning
confidence: 99%
“…[9][10][11] Oboh and Lamango purified the PMPMEase from pig liver and identified the 57 kDa protein as Sus scrofa carboxylesterase (pig liver esterase) after proteome analysis and Mascot database search. 12 The specific PMPMEase substrate, benzoyl-glycyl-farnesyl-cysteine methyl ester (BzGFCM) was synthesized 13 and it could be shown that this can be hydrolysed by the purified PMPMEase from pig liver. 12 As our group has succeeded in the past to identify, clone and functionally express several isoenzymes 14,15 of PLE, we report here also on the activity of the distinct isoenzymes in the hydrolysis of BzGFCM.…”
Section: Introductionmentioning
confidence: 99%